Quartz fiber joint glue based on spindle oil and preparation method thereof

By using quartz fiber joint glue based on spindle oil, the existing glue problems such as insufficient bonding, slow penetration speed and toxicity are solved, and the effects of non-toxic, strong adhesive, fast penetration and low cost are achieved, ensuring the product flatness and no chromatic difference.

CN119505760APending Publication Date: 2025-02-25HENAN SHENJIU TIANHANG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311031755.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing quartz fiber joint glue has problems such as insufficient adhesion, slow penetration, toxicity, pollution of the environment, endangering workers' health and leading to product color difference.

Method used

Quartz fiber joint glue based on spindle oil is used, and its formulation includes degluing agent, spindle oil and polymethyl methacrylate molding powder to form a colorless, transparent viscous colloid through physical and chemical reaction.

Benefits of technology

It realizes non-toxic, strong adhesive, fast penetration, non-stick hand and low cost glue, ensuring the flatness and color difference of quartz fiber products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to quartz fiber joint glue based on spindle oil and a preparation method thereof. The glue comprises the following components: 70-85% of dispergator, 8-16% of spindle oil and 10-20% of polymethyl methacrylate molding powder, and during preparation, a set amount of dispergator is added into a preparation barrel and stirred; slowly adding a set amount of spindle oil into the preparation barrel, and stirring for 5 minutes; and slowly adding a set amount of polymethyl methacrylate molding powder into the preparation barrel, and continuously stirring until the polymethyl methacrylate molding powder is completely dissolved, no white particles exist, and the solution is completely transparent and viscous. The adhesive has the advantages of no toxicity, small smell, simple and easily available formula, low cost, convenience in preparation and operation, no environmental pollution, no harm to human health, strong adhesion to quartz fiber yarns, high permeation speed, no hand sticking, good surface smoothness of the bonded quartz fiber product, no color difference at the bonded part after resin permeation compared with the color of quartz fiber, and no pollution to the environment. And the prepared composite material has no obvious color difference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to spindle oil-based quartz fiber joint glue and a preparation method thereof. Background Art

[0002] Quartz fiber is a woven material used for textile, weaving, and three-dimensional weaving. It can be made into quartz fiber yarn, which has high strength, high temperature resistance, heat insulation, electrical insulation, and good chemical stability. It has a wide range of applications in high temperature resistance, heat insulation, filtration, and flame retardancy. Quartz fiber yarn can be woven into quartz fiber cloth, belts, sleeves, etc., and can also be used as a reinforcing material for composite materials.

[0003] However, quartz fiber yarn also has the disadvantages of being brittle and not wear-resistant, especially during processing, it is easy to wear and break, which leads to yarn fuzzing and reduced strength. Therefore, quartz fiber yarn often breaks during processing, which requires the use of special joint glue to connect quartz fiber yarn.

[0004] However, the current quartz fiber factories, glass fiber factories and basalt fiber factories use traditional dibutyl phthalate type joint glue, which has a complex formula, high cost, and is toxic. It will pollute the environment and endanger the health of workers. More importantly, its bonding force is not very strong and the penetration speed is slow. The surface flatness of the quartz fiber bonded with it is poor, and there is color difference after bonding, especially after it is made into a composite material, there is color difference at the bonding point of the yarn, which affects the product quality.

[0005] On the other hand, dibutyl phthalate has been banned by the European Union because it has been identified as an environmental hormone that can cause cancer in animal liver tissue and disrupt the endocrine system. When it is subsequently incinerated, it will release large amounts of chlorine, vinyl chloride, dioxins and other toxic substances. Summary of the invention

[0006] The purpose of the present invention is to provide a spindle oil-based quartz fiber joint glue which is non-toxic, has strong bonding force, fast penetration, is non-sticky and has low cost; the purpose of the present invention is also to provide a preparation method of the above-mentioned spindle oil-based quartz fiber joint glue.

[0007] The technical scheme of the quartz fiber joint glue based on spindle oil of the present invention is as follows: the quartz fiber joint glue based on spindle oil, the joint glue is made of the following raw materials in mass percentage: Glue dissolving agent 70-85%; Spindle oil 8-16%; Polymethyl methacrylate molding powder 10-20%.

[0008] When the spindle oil-based quartz fiber joint glue of the present invention is used to make joints of quartz fiber products, the spindle oil can react physically and chemically with the polymethyl methacrylate molding powder, and under the dissolving action of the dissolving agent, a colorless and completely transparent viscous colloid is formed. The glue itself is non-toxic, does not pollute the environment, does not harm the health of workers, and the material is easy to obtain, and the cost is significantly reduced. Due to the completely colorless and transparent characteristics, the color of the bonded quartz fiber will not be increased or changed, so the quartz fiber products bonded by the glue have no color difference. Furthermore, due to the effective effect of the spindle oil on the lubrication and softening of the polymethyl methacrylate molding powder, the overall bonding force of the glue is significantly enhanced, and the permeability is also significantly improved. At the same time, after the bonding is solidified, the surface of the product is very smooth and has good flatness. Moreover, if it is accidentally left on the hands, it is also very convenient to clean up due to its non-sticky characteristics.

[0009] Preferably, the spindle oil is No. 5 spindle oil.

[0010] Preferably, the polymethyl methacrylate molding powder is 613 polymethyl methacrylate molding powder.

[0011] Preferably, the viscosity of the dissolving agent is 2-5 cps, and the effective substance is ≥35%.

[0012] Preferably, the density of the No. 5 spindle oil at 15°C is 0.812 g / cm³.

[0013] Preferably, the kinematic viscosity of the No. 5 spindle oil at 40° C. is 4.9 cSt.

[0014] Preferably, the 613 polymethyl methacrylate molding powder is in powder form, and the PMMA microsphere particle size is 250-300 mesh.

[0015] The technical scheme of the preparation method of the spindle oil-based quartz fiber joint glue of the present invention is as follows: Add a set amount of dissolving agent into the preparation barrel and stir; Slowly add the set amount of spindle oil into the preparation barrel and stir for 5 minutes; Slowly add a set amount of polymethyl methacrylate molding powder into the preparation bucket and stir continuously until the polymethyl methacrylate molding powder is completely dissolved, no white particles are left, and the solution is completely transparent and viscous.

[0016] Compared with traditional joint glue, its preparation process is very simple, and because it is non-toxic and does not require closed operation, the operation is very convenient and fast, and the preparation efficiency is relatively high.

[0017] In summary, the present application has the following beneficial effects: non-toxic, low odor, simple and easy to obtain formula, low cost, convenient configuration and operation, no pollution to the environment, no harm to human health, strong adhesion to quartz fiber yarn, fast penetration speed, non-sticky, good surface smoothness of the bonded quartz fiber product, no color difference at the bonding point after resin penetration compared with the color of quartz fiber, and no obvious color difference after being made into a composite material. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all the embodiments.

[0020] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0021] The corresponding disintegrator, No. 5 spindle oil and 613 polymethyl methacrylate molding powder in the following examples can all be purchased commercially, wherein: When choosing a debonding agent, it is best to meet the following conditions: the viscosity of the debonding agent is 2-5cps, and the effective substance is ≥35%; the debonding agent (also known as debonding agent or debonding agent) is a synthetic chemical agent that can quickly, conveniently and effectively remove chemical components such as grease and glue, and play a role in cleaning the surface. The debonding agent is made by mixing turpentine, rosin water, 120# gasoline, kerosene, etc. The chemical components include: benzene, toluene, xylene, acetone, ethyl acetate, butyl acetate, ethanol, etc.

[0022] When choosing No. 5 spindle oil, it is best to meet the following conditions: the density of No. 5 spindle oil at 15°C is 0.812g / cm³, and the kinematic viscosity at 40°C is 4.9cSt; spindle oil is a low-viscosity spindle bearing oil (also called spindle oil), which is made of highly refined base mineral oil and refined with a variety of high-efficiency additives such as cleaning, dispersing, anti-wear, anti-oxidation, anti-corrosion, and anti-foaming; When choosing 613 polymethyl methacrylate molding powder, it is best to meet the following conditions: 613 polymethyl methacrylate molding powder is in powder form, and the PMMA microsphere particle size is 250-300 mesh. Polymethyl methacrylate molding powder is a powdery or granular homopolymer or copolymer with methyl methacrylate as the main raw material. It is also called organic glass molding compound. It is an important variety of organic glass.

[0023] Embodiment 1 of the quartz fiber joint glue based on spindle oil of the present invention: The quartz fiber joint glue based on spindle oil of this embodiment is composed of the following components in terms of weight percentage: Glue dissolving agent 75%; No. 5 spindle oil 8%; 613 polymethyl methacrylate molding powder 17%.

[0024] Prepare according to the following method: First, add the prepared and weighed amount of dissolving agent into the preparation bucket and start stirring; Slowly add No. 5 spindle oil accurately weighed in proportion into the preparation barrel and stir continuously for 5 minutes; Slowly add the 613 polymethyl methacrylate molding powder accurately weighed in proportion into the preparation barrel and stir continuously until the 613 polymethyl methacrylate molding powder is completely dissolved without white particles, and the solution is completely transparent and viscous, which becomes the required quartz fiber joint glue based on spindle oil. Finally, fill the prepared joint glue into a sealed plastic barrel.

[0025] Test Example 1 using the spindle oil-based quartz fiber joint glue of Example 1: The following specifications of quartz fiber yarn are selected as the test material, with a linear density of 72Tex, a diameter of 7.5μm, a twist of 50S, and twisted yarn. The spindle oil-based quartz fiber joint glue of Example 1 is used to perform joint bonding on the test material and for a period of time after bonding, and the following indicators are tested respectively: bonding strength, penetration speed, color difference, ease of operation, surface flatness, and the bonding between quartz fiber products and resin. The test results are as follows: From the above results, it can be seen that after using the glue of Example 1, the bonding strength of the product exceeds the standard, the penetration speed during the bonding process is less than the standard minimum value, the penetration speed is fast, and there is no white silk or delamination after bonding, which proves that the permeability is good, the bonding is good, the surface is flat and has no protrusions, which proves that the flatness is good.

[0026] Embodiment 2 of the quartz fiber joint glue based on spindle oil of the present invention: The quartz fiber joint glue based on spindle oil of this embodiment is composed of the following components in terms of weight percentage: Glue dissolving agent 80%; No. 5 spindle oil 7%; 613 polymethyl methacrylate molding powder 13%.

[0027] Prepare according to the following method: First, add the prepared and weighed amount of dissolving agent into the preparation bucket and start stirring; Slowly add No. 5 spindle oil accurately weighed in proportion into the preparation barrel and stir continuously for 5 minutes; Slowly add the 613 polymethyl methacrylate molding powder accurately weighed in proportion into the preparation barrel and stir continuously until the 613 polymethyl methacrylate molding powder is completely dissolved without white particles, and the solution is completely transparent and viscous, which becomes the required quartz fiber joint glue based on spindle oil. Finally, fill the prepared joint glue into a sealed plastic barrel.

[0028] Test Example 2 using the spindle oil-based quartz fiber joint glue of Example 2: The following specifications of quartz fiber yarn were selected as the test material, with a linear density of 72Tex, a diameter of 7.5μm, a twist of 50S, and twisted yarn. The spindle oil-based quartz fiber joint glue of Example 2 was used to perform joint bonding on the test material and for a period of time after bonding, and the following indicators were tested respectively: bonding strength, penetration speed, color difference, ease of operation, surface flatness, and the bonding between quartz fiber products and resin. The test results are as follows: From the above results, it can be seen that after using the glue of Example 2, the bonding strength of the product exceeds the standard, the penetration rate during the bonding process is less than the standard minimum value, the penetration rate is fast, and there is no white silk or delamination after bonding, which proves that the permeability is good, the bonding is good, the surface is flat and has no protrusions, which proves that the flatness is good.

[0029] Embodiment 3 of the quartz fiber joint glue based on spindle oil of the present invention: The quartz fiber joint glue based on spindle oil of this embodiment is composed of the following components in terms of weight percentage: Glue dissolving agent 70%; No. 5 spindle oil 15%; 613 polymethyl methacrylate molding powder 15%.

[0030] Prepare according to the following method: First, add the prepared and weighed amount of dissolving agent into the preparation bucket and start stirring; Slowly add No. 5 spindle oil accurately weighed in proportion into the preparation barrel and stir continuously for 5 minutes; Slowly add the 613 polymethyl methacrylate molding powder accurately weighed in proportion into the preparation barrel and stir continuously until the 613 polymethyl methacrylate molding powder is completely dissolved without white particles, and the solution is completely transparent and viscous, which becomes the required quartz fiber joint glue based on spindle oil. Finally, fill the prepared joint glue into a sealed plastic barrel.

[0031] Test Example 3 using the spindle oil-based quartz fiber joint glue of Example 3: The following specifications of quartz fiber yarn were selected as the test material, with a linear density of 72Tex, a diameter of 7.5μm, a twist of 50S, and twisted yarn. The spindle oil-based quartz fiber joint glue of Example 3 was used to perform joint bonding on the test material and for a period of time after bonding, and the following indicators were tested respectively: bonding strength, penetration speed, color difference, ease of operation, surface flatness, and the bonding between quartz fiber products and resin. The test results are as follows: Serial number Detection indicators unit standard Test Results 1 Bond strength N / Tex ≥0.3 0.412 2 Penetration speed Second ≤8 6.5 3 Operational convenience point ≤1 0.68 4 Chromatic Aberration Compared with quartz fiber, there is no color difference at the bonding point after resin saturation conform to 5 Surface smoothness of quartz fiber products Smooth surface without protrusions conform to 6 Combination of quartz fiber products with resin No white silk, no delamination conform to From the above results, it can be seen that after using the glue of Example 3, the bonding strength of the product exceeds the standard, the penetration speed during the bonding process is less than the standard minimum value, the penetration speed is fast, and there is no white silk or delamination after bonding, which proves that the permeability is good, the bonding is good, the surface is flat and has no protrusions, which proves that the flatness is good.

[0032] In other embodiments, No. 5 spindle oil may be replaced by other brands of spindle oil, and 613 polymethyl methacrylate molding powder may be replaced by other brands of polymethyl methacrylate molding powder.

[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. The patent protection scope of the present invention shall be based on the claims. All equivalent structural changes made using the contents of the specification of the present invention should also be included in the protection scope of the present invention.

Claims

1. Spindle oil-based quartz fiber joint glue, characterized in that: The joint glue is prepared from the following raw materials in percentage by mass: Glue dissolving agent 70-85%; Spindle oil 8-16%; Polymethyl methacrylate molding powder 10-20%.

2. The quartz fiber joint glue based on spindle oil according to claim 1, characterized in that: The spindle oil is No. 5 spindle oil.

3. The spindle oil-based quartz fiber joint glue according to claim 1, characterized in that: The polymethyl methacrylate molding powder is 613 polymethyl methacrylate molding powder.

4. The spindle oil-based quartz fiber joint glue according to claim 1, characterized in that: The viscosity of the dissolving agent is 2-5 cps, and the effective substance is ≥35%.

5. The spindle oil-based quartz fiber joint glue according to claim 2, characterized in that: The density of the No. 5 spindle oil at 15°C is 0.812 g / cm³.

6. The spindle oil-based quartz fiber joint glue according to claim 2 or 5, characterized in that: The kinematic viscosity of the No. 5 spindle oil at 40° C. is 4.9 cSt.

7. The spindle oil-based quartz fiber joint glue according to claim 3, characterized in that: The 613 polymethyl methacrylate molding powder is in powder form, and the PMMA microsphere particle size is 250-300 meshes.

8. The method for preparing the spindle oil-based quartz fiber joint glue according to any one of claims 1 to 7, characterized in that: Follow these steps: Add a set amount of dissolving agent into the preparation barrel and stir; Slowly add the set amount of spindle oil into the preparation barrel and stir for 5 minutes; Slowly add a set amount of polymethyl methacrylate molding powder into the preparation bucket and stir continuously until the polymethyl methacrylate molding powder is completely dissolved, no white particles are left, and the solution is completely transparent and viscous.